Resin composition, prepreg, and circuit board
Patent Information
- Application Number
- CN202211217797.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-09-30
AI Technical Summary
[0003]然而,采用环氧树脂、固化剂以及填料为主要成分的树脂组合物制备电路基板时,电路基板的介电损耗较高,无法满足上述需求
[0022]环烯烃树脂的介电损耗和介电常数低,本发明的树脂组合物中,通过采用侧链具有能够与所述环氧树脂反应的反应基团的环烯烃树脂作为固化剂,同时限定第一环氧树脂、第二环氧树脂与环烯烃树脂的溶解度参数关系,一方面,能够提升环氧树脂与环烯烃树脂之间的相容性,另一方面,环烯烃树脂能够与环氧树脂发生反应。进而,采用所述树脂组合物制备的电路基板具有极低的介电损耗,同时还具有优异的耐热性、尺寸稳定性和耐CAF性能。
Smart Images

Figure SMS_7 
Figure SMS_8 
Figure SMS_9
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic industry technology, and in particular to resin compositions, prepregs, and circuit boards. Background Technology
[0002] With the advent of the 5G / 6G era, autonomous driving, automotive collision avoidance systems, high-speed, high-capacity memory, positioning systems, and the Internet of Things are being widely applied. These applications place demands on electronic materials and components for high-frequency, high-speed signal transmission and large-capacity storage, while also requiring increasingly higher quality and integrity in signal transmission. Currently, applications are researching high-frequency signal transmission at 112G, 112G+, and 224G. As the carrier of these signals, copper-clad laminates and other circuit boards must possess extremely low dielectric loss to meet the aforementioned signal integrity and high-frequency transmission requirements. Furthermore, considering the harsh environments in which these devices operate, the circuit boards must also possess excellent heat resistance.
[0003] However, when circuit boards are prepared using resin compositions with epoxy resin, curing agent and filler as the main components, the dielectric loss of the circuit boards is high, which cannot meet the above requirements. Summary of the Invention
[0004] Therefore, it is necessary to provide a resin composition, a prepreg, and a circuit board to address the above problems. The circuit board prepared using the resin composition has extremely low dielectric loss, as well as excellent heat resistance, dimensional stability, and CAF resistance.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is: a resin composition comprising epoxy resin, filler, curing agent and solvent;
[0006] The epoxy resin comprises a first epoxy resin and a second epoxy resin, wherein the first epoxy resin comprises a greater weight percentage of the first epoxy resin in the resin composition than the second epoxy resin in the resin composition, and the solubility parameter of the first epoxy resin is δ1, 8.55 (cal / cm³). 3 ) 1 / 2 ≤δ1≤9.40(cal / cm 3 ) 1 / 2 The solubility parameter of the second epoxy resin is δ2, 8.05 (cal / cm³). 3 ) 1 / 2 ≤δ2≤9.10(cal / cm 3 ) 1 / 2 And δ1 > δ2;
[0007] The curing agent comprises at least a cyclic olefin resin, which is selected from cyclic olefin copolymers and / or cyclic olefin polymers, and the side chains of the cyclic olefin resin have reactive groups capable of reacting with the epoxy resin. The solubility parameter of the cyclic olefin resin is δ3, 7.6 (cal / cm³). 3 ) 1 / 2 ≤δ3≤8.6(cal / cm 3 ) 1 / 2 And δ2>δ3.
[0008] In one embodiment, the first epoxy resin is selected from at least one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, linear phenolic epoxy resin, brominated bisphenol A type epoxy resin, and brominated phenolic epoxy resin, and the second epoxy resin is selected from at least one of aliphatic epoxy resin with a main chain of straight-chain alkane structure and end groups of epoxy groups or glycidyl ether epoxy resin with a main chain of aliphatic diol structure and end groups of epoxy groups.
[0009] In one embodiment, the main chain of the second epoxy resin is an alkane with a carbon chain length greater than or equal to 8.
[0010] In one embodiment, the cyclic olefin resin is selected from cyclic olefin copolymers and / or cyclic olefin polymers.
[0011] In one embodiment, the reactive groups of the side chains of the cyclic olefin resin are selected from at least one of hydroxyl, amino, or acid anhydride.
[0012] In one embodiment, the molecular weight of the cyclic olefin resin is 500-5000.
[0013] In one embodiment, the reactive group equivalent of the cyclic olefin resin is 300 g / eq-1200 g / eq, and the ratio of the epoxy group equivalent of the epoxy resin to the reactive group equivalent of the cyclic olefin resin is 0.8:1-1.3:1.
[0014] In one embodiment, based on 100 parts by weight of the first epoxy resin, the amount of the second epoxy resin is 10 to 50 parts by weight, and the amount of the cycloolefin resin is 40 to 125 parts by weight.
[0015] In one embodiment, the resin composition further includes a filler, and the filler is used in an amount of 90 to 250 parts by weight based on 100 parts by weight of the first epoxy resin.
[0016] In one embodiment, the curing agent further includes an auxiliary curing agent selected from at least one of phenolic resin, 3,3'-diaminodiphenyl sulfone, amine curing agent, and hydroxyl curing agent. The amount of the auxiliary curing agent is 10 to 40 parts by weight based on 100 parts by weight of the first epoxy resin.
[0017] The present invention also discloses a semi-cured sheet, which is formed by the resin composition on a reinforcing material and then dried.
[0018] In one embodiment, when the differential scanning calorimetry method is used for testing, the highest reaction temperature of the prepreg is 130°C-170°C.
[0019] And / or, the reaction enthalpy of the semi-cured sheet is 25 J / g-50 J / g.
[0020] The present invention also discloses a circuit board, the circuit board comprising a dielectric layer and a conductive layer disposed on at least one surface of the dielectric layer, wherein the dielectric layer is formed by pressing one or at least two laminated prepreg sheets.
[0021] In one embodiment, the glass transition temperature of the circuit board is 170°C-230°C, and the elongation at break is 0.5%-1.5%.
[0022] Cycloolefin resins have low dielectric loss and dielectric constant. In the resin composition of the present invention, by using a cycloolefin resin with reactive groups on its side chains that can react with the epoxy resin as a curing agent, and by defining the solubility parameter relationship between the first epoxy resin, the second epoxy resin, and the cycloolefin resin, the compatibility between the epoxy resin and the cycloolefin resin can be improved, and the cycloolefin resin can react with the epoxy resin. Furthermore, the circuit board prepared using the resin composition exhibits extremely low dielectric loss, as well as excellent heat resistance, dimensional stability, and CAF resistance. Detailed Implementation
[0023] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional scope of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.
[0025] Cyclic olefin copolymers (COC) and cyclic olefin polymers (COP) have low dielectric loss and dielectric constant. However, COC / COP has a high molecular weight (around 100,000 Mn) and low polarity, leading to macroscopic compatibility issues with epoxy resins. Directly adding COC / COP to epoxy resin compositions can cause resin phase separation, resulting in decreased heat resistance of the circuit board and even CAF failure. Furthermore, COC / COP has high rigidity and a high glass transition temperature (Tg), which reduces the flexibility of the circuit board. Therefore, cyclic olefin copolymers cannot be directly added to epoxy resin compositions.
[0026] Therefore, the resin composition provided by the present invention includes an epoxy resin, a curing agent, and a solvent, wherein the epoxy resin includes a first epoxy resin and a second epoxy resin, the first epoxy resin having a greater weight percentage in the resin composition than the second epoxy resin, and the solubility parameter of the first epoxy resin being δ1, 8.55 (cal / cm³). 3 ) 1 / 2 ≤δ1≤9.40(cal / cm 3 ) 1 / 2 The solubility parameter of the second epoxy resin is δ2, 8.05 (cal / cm³). 3 ) 1 / 2 ≤δ2≤9.10(cal / cm 3 ) 1 / 2 And δ1 > δ2; the curing agent includes at least a cyclic olefin resin, and the side chain of the cyclic olefin resin has reactive groups capable of reacting with the epoxy resin, and the solubility parameter of the cyclic olefin resin is δ3, 7.6 (cal / cm³). 3 ) 1 / 2 ≤δ3≤8.6(cal / cm 3 ) 1 / 2 And δ2>δ3.
[0027] Therefore, by using a cycloolefin resin with reactive groups on its side chains that can react with the epoxy resin as a curing agent, and by defining the solubility parameter relationship between the first epoxy resin, the second epoxy resin, and the cycloolefin resin, the compatibility between the epoxy resin and the cycloolefin resin can be improved, and the cycloolefin resin can react with the epoxy resin. Consequently, the circuit board prepared using the resin composition exhibits extremely low dielectric loss, as well as excellent heat resistance, dimensional stability, and CAF resistance.
[0028] Optionally, the first epoxy resin is selected from at least one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, linear phenolic epoxy resin, brominated bisphenol A type epoxy resin, and brominated phenolic epoxy resin.
[0029] In the resin composition, the second epoxy resin can improve the compatibility between the first epoxy resin and the cyclic olefin resin, and also mitigate the problem of decreased flexibility of the circuit board caused by the introduction of the cyclic olefin resin. Therefore, in some embodiments, the amount of the second epoxy resin is preferably 10%-50% of the mass of the first epoxy resin.
[0030] Optionally, the second epoxy resin is selected from at least one of an aliphatic epoxy resin with a main chain of straight-chain alkane and end groups of epoxy groups, or a glycidyl ether epoxy resin with a main chain of aliphatic diol and end groups of epoxy groups. Both of these epoxy resins have high flexibility due to their main chains consisting of C-C single bonds. Adding them to the resin composition can further reduce the stiffness of the circuit board made from them, improve its flexibility, and increase its bending strength. Simultaneously, the epoxy groups at both ends and the low polarity of the main chain result in better compatibility with the first epoxy resin and the cyclic olefin resin.
[0031] The structural formula of the aliphatic epoxy resin with a main chain of straight-chain alkane and end groups of epoxy groups is shown in formula (1), and the structural formula of the glycidyl ether epoxy resin with a main chain of aliphatic diol and end groups of epoxy groups is shown in formula (2).
[0032] Equation (1), Equation (2).
[0033] Furthermore, the main chain of the second epoxy resin is preferably an alkane with a carbon chain length greater than or equal to 8, that is, a≥8 in formula (1) and R in formula (2) is an alkane with a carbon chain length greater than or equal to 8, thereby improving the flexibility of the circuit board.
[0034] Optionally, the reactive group R of the side chain of the cyclic olefin resin is selected from at least one of hydroxyl, amino or acid anhydride. Further, the cyclic olefin resin is selected from cyclic olefin copolymers and / or cyclic olefin polymers, with structural formulas as shown in formulas (3) and (4), respectively, where the values of n, m, x, y and z are controlled by the molecular weight and functional group equivalent.
[0035] Equation (3), Equation (4).
[0036] Optionally, the molecular weight of the cyclic olefin resin is preferably 500-5000, which is beneficial to further improve the crosslinking degree between resins, thereby further improving the mechanical properties of the circuit board.
[0037] Optionally, the reactive group equivalent of the cyclic olefin resin is 300 g / eq-1200 g / eq, and the ratio of the epoxy group equivalent of the epoxy resin to the reactive group equivalent of the cyclic olefin resin is 0.8:1-1.3:1. This also helps to further improve the crosslinking degree between resins, thereby further improving the dielectric loss, mechanical properties, and Tg of the circuit board. It can be understood that the epoxy equivalent of the epoxy resin includes the epoxy equivalent of the first epoxy resin and the epoxy equivalent of the second epoxy resin.
[0038] Optionally, cycloolefin resins with reactive groups on the side chains that can react with the epoxy resin can be prepared by referring to the following method: using norbornene-2-methanol, norbornene-2-methylamine, norbornene anhydride, dicyclopentadiene, functionalized dicyclopentadiene, etc. as monomers, COP with reactive groups on the side chains that can react with the epoxy resin is synthesized by ring-opening metathesis polymerization (ROMP).
[0039] Optionally, the solvent is selected from at least one of toluene, butanone, xylene, and propylene glycol methyl ether.
[0040] Optionally, based on 100 parts by weight of the first epoxy resin, the amount of the second epoxy resin is 10 to 50 parts by weight, and the amount of the cyclic olefin resin is 40 to 125 parts by weight.
[0041] Optionally, the resin composition further includes filler, and the amount of filler is 90 to 250 parts by weight, based on 100 parts by weight of the first epoxy resin.
[0042] The filler is selected from at least one of SiO2, Al2O3, TiO2, ZnO, MgO, Bi2O3, AlN, BN, Si3N4, SiC, Al(OH)3, Mg(OH)2, Mg2TiO4, Bi2(TiO3)3, PbTiO3, NiTiO3, CaTiO3, ZnTiO3, Zn2TiO4, BaSnO3, Bi2(SnO3)3, CaSnO3, PbSnO3, MgSnO3, SrSnO3, ZnSnO3, BaZrO3, CaZrO3, PbZrO3, MgZrO3, SrZrO3, ZnZrO3, lead magnesium niobate, iron tungsten niobate, lead zirconate titanate, talc, bentonite, and silica powder. Furthermore, a coupling agent can be added to improve the compatibility between the filler and the resin.
[0043] Optionally, the curing agent further includes an auxiliary curing agent, which is selected from at least one of phenolic resin, 3,3'-diaminodiphenyl sulfone, amine curing agent, and hydroxyl curing agent. The amount of the auxiliary curing agent is 10 to 40 parts by weight based on 100 parts by weight of the first epoxy resin.
[0044] The present invention also discloses a semi-cured sheet, which is formed by the resin composition on a reinforcing material and then dried.
[0045] Optionally, the reinforcing material is preferably glass fiber cloth, and the resin composition is formed on the reinforcing material by coating, impregnation, or other methods, and the solvent in the resin composition is removed by drying. Specifically, the drying temperature is preferably 150℃-200℃, and the drying time is preferably 100s-300s.
[0046] The semi-cured sheet made using the resin composition of the present invention has a maximum reaction temperature of 130°C-170°C when tested by differential scanning calorimetry (DSC), and / or the reaction enthalpy of the semi-cured sheet is 25 J / g-50 J / g.
[0047] The present invention also discloses a circuit board, the circuit board comprising a dielectric layer and a conductive layer disposed on at least one surface of the dielectric layer, wherein the dielectric layer is formed by pressing one or at least two laminated prepreg sheets.
[0048] Specifically, the conductive layer is preferably copper foil, and the circuit board is a copper-clad laminate.
[0049] The circuit board made using the prepreg of the present invention has a glass transition temperature of 170℃-230℃ and an elongation at break of 0.5%-1.5%, as tested.
[0050] The resin composition, prepreg, and circuit board will be further described below through specific embodiments.
[0051] Example 1
[0052] The resin composition of this embodiment includes 100 parts by weight of dicyclopentadiene phenol epoxy resin, 22.6 parts by weight of 1,2,16,17-diepoxyheptadecane, 79.8 parts by weight of a cyclic olefin copolymer with hydroxyl side chains, 2.4 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 23 parts by weight of 4,4'-diaminophenyl sulfone, 53.6 parts by weight of aluminum hydroxide, 124.6 parts by weight of silica, 40 parts by weight of propylene glycol monomethyl ether, 60.5 parts by weight of acetone, and 60.5 parts by weight of toluene.
[0053] The solubility parameter δ1 of the dicyclopentadiene phenol epoxy resin is 8.74 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 260 g / eq; the solubility parameter δ² of 1,2,16,17-diepoxyheptadecane is 8.43 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 127 g / eq; the solubility parameter δ3 of the cyclic olefin copolymer with hydroxyl side chains (structural formula as shown in formula (3), n=21, m=3) is 7.91 (cal / cm). 3 ) 1 / 2 The hydroxyl equivalent is 600 g / eq, and the molecular weight is 2398 g / mol.
[0054] 1078E fiberglass cloth is impregnated in the above resin composition and then baked at a temperature range of 170℃-172℃ for 170s-180s to obtain a semi-cured sheet.
[0055] Six of the above-mentioned prepreg sheets are stacked together, and 1oz copper foil is attached to both the top and bottom sides. After pressing, a circuit board is obtained.
[0056] Example 2
[0057] The resin composition of this embodiment includes 100 parts by weight of bisphenol A epichlorohydrin resin, 22.6 parts by weight of 1,2,16,17-diepoxyheptadecane, 79.8 parts by weight of a cyclic olefin copolymer with hydroxyl side chains, 2.4 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 23 parts by weight of 4,4'-diaminophenyl sulfone, 53.6 parts by weight of aluminum hydroxide, 124.6 parts by weight of silica, 40 parts by weight of propylene glycol monomethyl ether, 60.5 parts by weight of acetone, and 60.5 parts by weight of toluene.
[0058] The solubility parameter δ1 of the bisphenol A epichlorohydrin resin is 9.1 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 187 g / eq; the solubility parameter δ² of 1,2,16,17-diepoxyheptadecane is 8.43 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 127 g / eq; the solubility parameter δ3 of the cyclic olefin copolymer with hydroxyl side chains (structural formula as shown in formula (3), n=21, m=3) is 7.91 (cal / cm). 3 ) 1 / 2 The hydroxyl equivalent is 600 g / eq, and the molecular weight is 2398 g / mol.
[0059] 1078E fiberglass cloth is impregnated in the above resin composition and then baked at a temperature range of 170℃-172℃ for 170s-180s to obtain a semi-cured sheet.
[0060] Six of the above-mentioned prepreg sheets are stacked together, and 1oz copper foil is attached to both the top and bottom sides. After pressing, a circuit board is obtained.
[0061] Example 3
[0062] The resin composition of this embodiment includes 100 parts by weight of dicyclopentadiene phenol epoxy resin, 22.6 parts by weight of 1,10-decylene glycol diglycidyl ether epoxy resin, 79.8 parts by weight of a cyclic olefin copolymer with hydroxyl side chains, 2.4 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 23 parts by weight of 4,4'-diaminophenyl sulfone, 53.6 parts by weight of aluminum hydroxide, 124.6 parts by weight of silica, 40 parts by weight of propylene glycol monomethyl ether, 60.5 parts by weight of acetone, and 60.5 parts by weight of toluene.
[0063] The solubility parameter δ1 of the dicyclopentadiene phenol epoxy resin is 8.74 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 260 g / eq; the solubility parameter δ2 of 1,10-decyl glycol diglycidyl ether epoxy resin is 8.63 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 136 g / eq; the solubility parameter δ3 of the cyclic olefin copolymer with hydroxyl groups in the side chain (structural formula as shown in formula (3), n=21, m=3) is 7.91 (cal / cm). 3 ) 1 / 2 The hydroxyl equivalent is 600 g / eq, and the molecular weight is 2398 g / mol.
[0064] 1078E fiberglass cloth is impregnated in the above resin composition and then baked at a temperature range of 170℃-172℃ for 170s-180s to obtain a semi-cured sheet.
[0065] Six of the above-mentioned prepreg sheets are stacked together, and 1oz copper foil is attached to both the top and bottom sides. After pressing, a circuit board is obtained.
[0066] Example 4
[0067] The resin composition of this embodiment includes 100 parts by weight of dicyclopentadiene phenol epoxy resin, 22.6 parts by weight of 1,14-tetradecyl alcohol diglycidyl ether epoxy resin, 79.8 parts by weight of a cyclic olefin copolymer with hydroxyl side chains, 2.4 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 23 parts by weight of 4,4'-diaminophenyl sulfone, 53.6 parts by weight of aluminum hydroxide, 124.6 parts by weight of silica, 40 parts by weight of propylene glycol monomethyl ether, 60.5 parts by weight of acetone, and 60.5 parts by weight of toluene.
[0068] The solubility parameter δ1 of the dicyclopentadiene phenol epoxy resin is 8.74 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 260 g / eq; the solubility parameter δ2 of 1,14-tetradecyl diglycidyl ether epoxy resin is 8.71 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 150 g / eq; the solubility parameter δ3 of the cyclic olefin copolymer with hydroxyl side chains (structural formula as shown in formula (3), n=21, m=3) is 7.91 (cal / cm). 3 ) 1 / 2 The hydroxyl equivalent is 600 g / eq, and the molecular weight is 2398 g / mol.
[0069] 1078E fiberglass cloth is impregnated in the above resin composition and then baked at a temperature range of 170℃-172℃ for 170s-180s to obtain a semi-cured sheet.
[0070] Six of the above-mentioned prepreg sheets are stacked together, and 1oz copper foil is attached to both the top and bottom sides. After pressing, a circuit board is obtained.
[0071] Example 5
[0072] The resin composition of this embodiment includes 100 parts by weight of dicyclopentadiene phenol epoxy resin, 22.6 parts by weight of 1,5-pentanediol diglycidyl ether epoxy resin, 79.8 parts by weight of a cyclic olefin copolymer with hydroxyl side chains, 2.4 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 23 parts by weight of 4,4'-diaminophenyl sulfone, 53.6 parts by weight of aluminum hydroxide, 124.6 parts by weight of silica, 40 parts by weight of propylene glycol monomethyl ether, 60.5 parts by weight of acetone, and 60.5 parts by weight of toluene.
[0073] The solubility parameter δ1 of the dicyclopentadiene phenol epoxy resin is 8.74 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 260 g / eq; the solubility parameter δ2 of 1,5-pentanediol diglycidyl ether epoxy resin is 8.13 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 102 g / eq; the solubility parameter δ3 of the cyclic olefin copolymer with hydroxyl groups in the side chain (structural formula as shown in formula (3), n=21, m=3) is 7.91 (cal / cm). 3 ) 1 / 2 The hydroxyl equivalent is 600 g / eq, and the molecular weight is 2398 g / mol.
[0074] 1078E fiberglass cloth is impregnated in the above resin composition and then baked at a temperature range of 170℃-172℃ for 170s-180s to obtain a semi-cured sheet.
[0075] Six of the above-mentioned prepreg sheets are stacked together, and 1oz copper foil is attached to both the top and bottom sides. After pressing, a circuit board is obtained.
[0076] Example 6
[0077] The resin composition of this embodiment includes 100 parts by weight of dicyclopentadiene phenol epoxy resin, 22.6 parts by weight of 1,14-tetradecyl alcohol diglycidyl ether epoxy resin, 79.8 parts by weight of a cyclic olefin copolymer with hydroxyl side chains, 2.4 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 23 parts by weight of 4,4'-diaminophenyl sulfone, 53.6 parts by weight of aluminum hydroxide, 124.6 parts by weight of silica, 40 parts by weight of propylene glycol monomethyl ether, 60.5 parts by weight of acetone, and 60.5 parts by weight of toluene.
[0078] The solubility parameter δ1 of the dicyclopentadiene phenol epoxy resin is 8.74 (cal / cm³). 3 ) 1 / 2The epoxy group equivalent is 260 g / eq; the solubility parameter δ2 of 1,14-tetradecyl diglycidyl ether epoxy resin is 8.71 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 150 g / eq; the solubility parameter δ3 of the cyclic olefin copolymer with hydroxyl side chains (structural formula as shown in formula (3), n=51, m=10) is 8.58 (cal / cm). 3 ) 1 / 2 The hydroxyl equivalent is 606 g / eq, and the molecular weight is 6065 g / mol.
[0079] 1078E fiberglass cloth is impregnated in the above resin composition and then baked at a temperature range of 170℃-172℃ for 170s-180s to obtain a semi-cured sheet.
[0080] Six of the above-mentioned prepreg sheets are stacked together, and 1oz copper foil is attached to both the top and bottom sides. After pressing, a circuit board is obtained.
[0081] Example 7
[0082] The resin composition of this embodiment includes 100 parts by weight of dicyclopentadiene phenol epoxy resin, 22.6 parts by weight of 1,2,16,17-diepoxyheptadecane, 79.8 parts by weight of a cyclic olefin copolymer with hydroxyl side chains, 2.4 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 23 parts by weight of 4,4'-diaminophenyl sulfone, 53.6 parts by weight of aluminum hydroxide, 124.6 parts by weight of silica, 40 parts by weight of propylene glycol monomethyl ether, 60.5 parts by weight of acetone, and 60.5 parts by weight of toluene.
[0083] The solubility parameter δ1 of the dicyclopentadiene phenol epoxy resin is 8.74 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 260 g / eq; the solubility parameter δ² of 1,2,16,17-diepoxyheptadecane is 8.43 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 127 g / eq; the solubility parameter δ3 of the cyclic olefin copolymer with hydroxyl side chains (structural formula as shown in formula (3), n=20, m=4) is 8.21 (cal / cm). 3 ) 1 / 2 The hydroxyl equivalent is 800 g / eq, and the molecular weight is 2414 g / mol.
[0084] 1078E fiberglass cloth is impregnated in the above resin composition and then baked at a temperature range of 170℃-172℃ for 170s-180s to obtain a semi-cured sheet.
[0085] Six of the above-mentioned prepreg sheets are stacked together, and 1oz copper foil is attached to both the top and bottom sides. After pressing, a circuit board is obtained.
[0086] Example 8
[0087] The resin composition of this embodiment includes 100 parts by weight of dicyclopentadiene phenol epoxy resin, 22.6 parts by weight of 1,2,16,17-diepoxyheptadecane, 79.8 parts by weight of a cyclic olefin copolymer with amino side chains, 2.4 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 23 parts by weight of 4,4'-diaminophenyl sulfone, 53.6 parts by weight of aluminum hydroxide, 124.6 parts by weight of silica, 40 parts by weight of propylene glycol monomethyl ether, 60.5 parts by weight of acetone, and 60.5 parts by weight of toluene.
[0088] The solubility parameter δ1 of the dicyclopentadiene phenol epoxy resin is 8.74 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 260 g / eq; the solubility parameter δ² of 1,2,16,17-diepoxyheptadecane is 8.43 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 127 g / eq; the solubility parameter δ3 of the cyclic olefin copolymer with amino side chains (structural formula as shown in formula (3), n=20, m=10) is 8.15 (cal / cm). 3 ) 1 / 2 The hydroxyl equivalent is 618 g / eq, and the molecular weight is 3091 g / mol.
[0089] 1078E fiberglass cloth is impregnated in the above resin composition and then baked at a temperature range of 170℃-172℃ for 170s-180s to obtain a semi-cured sheet.
[0090] Six of the above-mentioned prepreg sheets are stacked together, and 1oz copper foil is attached to both the top and bottom sides. After pressing, a circuit board is obtained.
[0091] Example 9
[0092] The resin composition of this embodiment includes 100 parts by weight of dicyclopentadiene phenol epoxy resin, 22.6 parts by weight of 1,2,16,17-diepoxyheptadecane, 79.8 parts by weight of a cyclic olefin polymer with hydroxyl groups only in the side chain, 2.4 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 23 parts by weight of 4,4'-diaminophenyl sulfone, 53.6 parts by weight of aluminum hydroxide, 124.6 parts by weight of silica, 40 parts by weight of propylene glycol monomethyl ether, 60.5 parts by weight of acetone, and 60.5 parts by weight of toluene.
[0093] The solubility parameter δ1 of the dicyclopentadiene phenol epoxy resin is 8.74 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 260 g / eq; the solubility parameter δ² of 1,2,16,17-diepoxyheptadecane is 8.43 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 127 g / eq; the solubility parameter δ3 of the cycloolefin polymer with only hydroxyl groups in the side chain (structural formula as shown in formula (4), x=17, y=6, z=4) is 7.91 (cal / cm). 3 ) 1 / 2 The hydroxyl equivalent is 300 g / eq, and the molecular weight is 4207 g / mol.
[0094] 1078E fiberglass cloth is impregnated in the above resin composition and then baked at a temperature range of 170℃-172℃ for 170s-180s to obtain a semi-cured sheet.
[0095] Six of the above-mentioned prepreg sheets are stacked together, and 1oz copper foil is attached to both the top and bottom sides. After pressing, a circuit board is obtained.
[0096] Example 10
[0097] The resin composition of this embodiment includes 100 parts by weight of dicyclopentadiene phenol epoxy resin, 22.6 parts by weight of 1,2,16,17-diepoxyheptadecane, 79.8 parts by weight of a cyclic olefin polymer with hydroxyl groups only in the side chain, 2.4 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 53.6 parts by weight of aluminum hydroxide, 124.6 parts by weight of silica, 40 parts by weight of propylene glycol monomethyl ether, 60.5 parts by weight of acetone, and 60.5 parts by weight of toluene.
[0098] The solubility parameter δ1 of the dicyclopentadiene phenol epoxy resin is 8.74 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 260 g / eq; the solubility parameter δ² of 1,2,16,17-diepoxyheptadecane is 8.43 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 127 g / eq; the solubility parameter δ3 of the cycloolefin polymer with only hydroxyl groups in the side chain (structural formula as shown in formula (4), x=17, y=6, z=4) is 7.91 (cal / cm). 3 ) 1 / 2 The hydroxyl equivalent is 300 g / eq, and the molecular weight is 4207 g / mol.
[0099] 1078E fiberglass cloth is impregnated in the above resin composition and then baked at a temperature range of 170℃-172℃ for 170s-180s to obtain a semi-cured sheet.
[0100] Six of the above-mentioned prepreg sheets are stacked together, and 1oz copper foil is attached to both the top and bottom sides. After pressing, a circuit board is obtained.
[0101] Example 11
[0102] The resin composition of this embodiment includes 100 parts by weight of dicyclopentadiene phenol epoxy resin, 22.6 parts by weight of 1,2,16,17-diepoxyheptadecane, 280 parts by weight of a cyclic olefin copolymer with hydroxyl side chains, 2.4 parts by weight of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 53.6 parts by weight of aluminum hydroxide, 124.6 parts by weight of silica, 40 parts by weight of propylene glycol monomethyl ether, 40 parts by weight of acetone, and 100.8 parts by weight of toluene.
[0103] The solubility parameter δ1 of the dicyclopentadiene phenol epoxy resin is 8.74 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 260 g / eq; the solubility parameter δ² of 1,2,16,17-diepoxyheptadecane is 8.43 (cal / cm³). 3 ) 1 / 2 The epoxy group equivalent is 127 g / eq; the solubility parameter δ3 of the cyclic olefin copolymer with hydroxyl side chains (structural formula as shown in formula (3), n=21, m=3) is 7.91 (cal / cm). 3 ) 1 / 2 The hydroxyl equivalent is 600 g / eq, and the molecular weight is 2398 g / mol.
[0104] 1078E fiberglass cloth is impregnated in the above resin composition and then baked at a temperature range of 170℃-172℃ for 170s-180s to obtain a semi-cured sheet.
[0105] Six of the above-mentioned prepreg sheets are stacked together, and 1oz copper foil is attached to both the top and bottom sides. After pressing, a circuit board is obtained.
[0106] Comparative Example 1
[0107] The only difference between Comparative Example 1 and Example 1 is that the first epoxy resin is selected from those with a solubility parameter of 9.7 (cal / cm³). 3 ) 1 / 2 The bisphenol A type phenolic epoxy resin has an epoxy group equivalent of 210 g / eq; when the resin composition of this comparative example is used for preparation, the resin composition exhibits phase separation and cannot be used to fabricate a circuit board.
[0108] Comparative Example 2
[0109] The only difference between Comparative Example 2 and Example 4 is that the first epoxy resin is selected from those with a solubility parameter of 8.55 (cal / cm³). 3 ) 1 / 2 The bisphenol A epichlorohydrin resin has an epoxy group equivalent of 300 g / eq.
[0110] Comparative Example 3
[0111] The only difference between Comparative Example 3 and Example 1 is that the cyclic olefin resin is selected from cyclic olefin copolymers with hydroxyl groups in the side chains (structural formula as shown in formula (3), n=51, m=10) with a solubility parameter δ3 of 8.58 (cal / cm). 3 ) 1 / 2 The hydroxyl equivalent is 606 g / eq, and the molecular weight is 6065 g / mol.
[0112] Comparative Example 4
[0113] The only difference between Comparative Example 4 and Example 1 is that the hydroxyl groups of the cyclic olefin copolymer are located on the main chain, with the structural formula shown below, where the hydroxyl equivalent is 600 g / eq, the molecular weight is 6051 g / mol, and the solubility parameter δ3 is 8.60 (cal / cm³). 3 ) 1 / 2 ;
[0114] .
[0115] Comparative Example 5
[0116] The only difference between Comparative Example 5 and Example 1 is that the cyclic olefin copolymer lacks hydroxyl groups in both the main chain and side chains. Its structural formula is shown below, where the hydroxyl equivalent is 600 g / eq, the molecular weight is 6000 g / mol, and the solubility parameter δ3 is 7.91 (cal / cm³). 3 ) 1 / 2 ;
[0117] .
[0118] Comparative Example 6
[0119] The only difference between Comparative Example 6 and Example 1 is that Comparative Example 6 does not contain a second epoxy resin.
[0120] The prepregs and circuit boards prepared according to the embodiments and comparative examples of the present invention were subjected to performance tests, and the results are shown in Tables 1 to 3.
[0121] Table 1: Test Results of Prepreg
[0122]
[0123] Table 2: Test Results of Circuit Board
[0124]
[0125] Table 3: Test Results of Circuit Board
[0126]
[0127] Comparing Example 4 with Example 3, it can be seen that the longer the chain length of the second epoxy resin, the higher the flexibility of the circuit board and the higher the elongation at break.
[0128] Comparing Example 5 with Example 3, it can be seen that the number of carbon atoms in the main chain of the second epoxy resin is less than 8, resulting in poorer flexibility and reduced elongation at break of the circuit board.
[0129] Comparing Example 6 and Example 4, it can be seen that increasing the molecular weight of the cycloolefin resin leads to a deterioration in the mechanical properties of the circuit board and a decrease in the elongation at break.
[0130] Comparing Example 7 with Example 1, it can be seen that the functional group equivalent of the cyclic olefin resin is increased, the number of side chain functional groups is reduced, the crosslinking density is reduced, the flexibility of the circuit board is increased, the elongation at break is increased, the glass transition temperature is reduced, and the dimensional stability is worse.
[0131] Comparing Example 11 with Example 1, it can be seen that without the use of an auxiliary curing agent, the amount of cyclic olefin resin added is higher, the dielectric loss of the circuit board is improved, the proportion of main chain cyclic olefin resin after curing is increased, the overall rigidity is improved, and the elongation at break is reduced. With a higher proportion of cyclic olefin resin, the reactivity is lower than that of the auxiliary curing agent, the degree of crosslinking is reduced, and the glass transition temperature is lower.
[0132] As can be seen from Comparative Example 1 and Example 11, the solubility parameter of the first epoxy resin is too large, and its compatibility with the second epoxy resin and cyclic olefin resin is poor, resulting in macroscopic phase separation.
[0133] As can be seen from Comparative Example 2 and Example 4, the solubility parameter of the second epoxy resin is greater than that of the first epoxy resin. The second epoxy resin does not play a role in improving compatibility, the CAF performance is reduced, and the heat resistance is worse.
[0134] As can be seen from Comparative Example 3, Example 6, and Example 1, the solubility parameter of the second epoxy resin is less than that of the cyclic olefin resin. The second epoxy resin does not play a role in improving compatibility, and the performance of CAF is reduced.
[0135] As can be seen from Comparative Example 4 and Example 1, the reactive groups of cyclic olefin resin are located on the main chain. When crosslinking reaction occurs, the steric hindrance is large, the degree of reaction is reduced, the dielectric loss of the circuit board deteriorates, the glass transition temperature decreases, and the elongation at break decreases.
[0136] As can be seen from Comparative Example 5 and Example 1, the cyclic olefin resin does not contain reactive groups, has poor compatibility with the first resin, and the heat resistance of the circuit board deteriorates, the glass transition temperature decreases, the dimensional stability deteriorates, and the CAF properties deteriorate.
[0137] As can be seen from Comparative Example 6 and Example 1, without the use of the second epoxy resin, the compatibility with cyclic olefin resins deteriorates, and the performance of CAF deteriorates.
[0138] The performance testing methods for the above embodiments and comparative examples are as follows:
[0139] Maximum reaction temperature and enthalpy of the prepreg: The prepreg was placed in a crucible and placed in a differential scanning calorimeter (DSC) for temperature rise test. Nitrogen gas was purged during the test for protection.
[0140] Dielectric loss (Df) of circuit board: IEC61189-721-2015, dielectric constant resonant ring test (SPDR), data taken at 10GHz;
[0141] Glass transition temperature (Tg): GB / T4722-2017 6.7.2, Dynamic thermomechanical analyzer (DMA);
[0142] CTE: IPC-TM-650 2.4.24, Static Thermomechanical Analyzer (TMA), testing the X-axis direction;
[0143] Elongation at break: Test method for tensile properties of fiber-reinforced plastics GB / T 1447-2015, universal electronic tensile testing machine;
[0144] CAF: The circuit board is fabricated into a printed circuit board and drilled. CAF resistance testing is performed according to IPC-TM-650 2.6.25.
[0145] Heat resistance: Immerse the circuit board in the solder bath for 10 seconds, remove it, cool it for 10 seconds, and then immerse it in the solder bath again. Repeat the above process.
[0146] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0147] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A resin composition, characterized in that, Includes epoxy resin, curing agent, and solvent; The epoxy resin includes a first epoxy resin and a second epoxy resin, wherein the solubility parameter of the first epoxy resin is δ1, 8.55 (cal / cm³). 3 ) 1 / 2 ≤δ1≤9.40(cal / cm 3 ) 1 / 2 The solubility parameter of the second epoxy resin is δ2, 8.05 (cal / cm³). 3 ) 1 / 2 ≤δ2≤9.10(cal / cm 3 ) 1 / 2 And δ1>δ2; The curing agent comprises at least a cyclic olefin resin, and the side chains of the cyclic olefin resin have reactive groups capable of reacting with the epoxy resin. The reactive group equivalent of the cyclic olefin resin is 300 g / eq-1200 g / eq, the ratio of the epoxy group equivalent of the epoxy resin to the reactive group equivalent of the cyclic olefin resin is 0.8:1-1.3:1, the reactive groups of the side chains of the cyclic olefin resin are selected from at least one of hydroxyl and amino groups, and the solubility parameter of the cyclic olefin resin is δ3, 7.6 (cal / cm³). 3 ) 1 / 2 ≤δ3≤8.6(cal / cm 3 ) 1 / 2 And δ2 > δ3; Based on 100 parts by weight of the first epoxy resin, the amount of the second epoxy resin is 10 to 50 parts by weight, and the amount of the cyclic olefin resin is 40 to 125 parts by weight.
2. The resin composition according to claim 1, characterized in that, The first epoxy resin is selected from at least one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, linear phenolic epoxy resin, and brominated bisphenol A type epoxy resin. The second epoxy resin is selected from at least one of aliphatic epoxy resin with a main chain of straight-chain alkane structure and end groups of epoxy groups or glycidyl ether epoxy resin with a main chain of aliphatic diol structure and end groups of epoxy groups.
3. The resin composition according to claim 1, characterized in that, The first epoxy resin is selected from brominated phenolic epoxy resin.
4. The resin composition according to claim 2, characterized in that, The main chain of the second epoxy resin is an alkyl group with a carbon chain length greater than or equal to 8.
5. The resin composition according to claim 1, characterized in that, The cyclic olefin resin is selected from cyclic olefin polymers.
6. The resin composition according to any one of claims 1-5, characterized in that, The resin composition further includes filler, and the amount of filler is 90-250 parts by weight based on 100 parts by weight of the first epoxy resin.
7. The resin composition according to any one of claims 1-5, characterized in that, The curing agent further includes an auxiliary curing agent, which is selected from at least one of amine curing agents and hydroxyl curing agents. The amount of the auxiliary curing agent is 10 to 40 parts by weight based on 100 parts by weight of the first epoxy resin.
8. A semi-cured sheet, characterized in that, The semi-cured sheet is obtained by forming the resin composition of any one of claims 1-7 onto a reinforcing material and then drying it.
9. The semi-cured sheet according to claim 8, characterized in that, When tested using differential scanning calorimetry, the highest reaction temperature of the prepreg is 130℃-170℃; And / or, the reaction enthalpy of the semi-cured sheet is 25 J / g-50 J / g.
10. A circuit board, characterized in that, The circuit board includes a dielectric layer and a conductive layer disposed on at least one surface of the dielectric layer, wherein the dielectric layer is formed by pressing one or at least two laminated prepreg sheets as described in claim 8 or 9.
11. The circuit board according to claim 10, characterized in that, The glass transition temperature of the circuit board is 170℃-230℃, and the elongation at break is 0.5%-1.5%.
Citation Information
Patent Citations
Preparation method of epoxy alloy material
CN104744671A
Hardener for epoxy resin and epoxy resin composition
CN1957012A
